Faktor Yang Berhubungan Dengan Stres Kerja Perawat Di Ruang Instalasi Gawat Darurat (IGD) dan Rawat Inap RSUD Daya Kota Makassar - A. Nurul Annisa S Sarwan; Ikhram Hardi; Nurbaeti (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Nurses in the Emergency Room and inpatient units of Daya Hospital, Makassar City, have a high workload and face a stressful work environment. This condition can trigger work stress, impacting the performance and quality of nursing services. Therefore, a study was conducted to determine whether 25 nurses experienced excessive workload, while the majority, namely 55 nurses, complained of excessive workload. This workload often leaves them feeling tired, mainly due to the demands of providing maximum patient care, which reduces their rest time. This study used a quantitative, analytical survey method and a cross-sectional design. The study population comprised all nurses working in the Emergency Room and inpatient units, totaling 25 and 77, respectively. Using a total sampling technique, all 102 nurses were selected as study respondents. Data were analyzed using the chi-square test at a 95% confidence level (α = 0.05). The results showed that the workload variable was significantly related to nurses' work stress levels (p = 0.014), and the physical work environment was also significantly related to work stress (p = 0.000). These results confirm that high workloads and an unfavorable physical work environment significantly increase job stress. Improved workload management, a better physical work environment, and organizational support are needed to reduce job stress among nurses at Daya Regional Hospital in Makassar City.